Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
r - reszta
n/6= x r 5 = x+5/6
n=6x+5
n^2/6 = (6x+5)²/6=(36x²+60x+25)/6=6x²+10x+4+1/6
n^2/6= 6x² + 10x + 4 r 1
n=3k+2
n²+2=(3k+2)²+2=9k²+12k+4+2=3*(3k²+4k+2)
1)
[tex]\frac{n}6=x+\frac56 /*6\\n=6x+5\\\\\frac{n^2}6=\frac{(6x+5)^2}6=\frac{36x^2+60x+25}6=6x^2+10x+\frac{25}6=6x^2+10x+4+\frac16\\\frac{n^2}6=6x^2+10x+4 \text{ reszta } 1[/tex]
2)
[tex]\frac{n}3=x+\frac23 /*3\\n=3x+2\\\\\frac{n^2+2}3=\frac{(3x+2)^2+2}3=\frac{9x^2+12x+4+2}3=\frac{9x^2+12x+6}3=\frac{3(3x^2+4x+2)}3=3x^2+4x+2\\\text{Liczba jest podzielna przez 3 bez reszty (brak ulamka w wyrazie wolnym)}[/tex]